Pengaruh Variasi Ukuran Tulangan Bambu Terhadap Kuat Lentur Panel Lapis Sirip Bambu dengan Takikan pada Permukaan Panel - Mohammad Taufik Hidayat (Rekayasa Sipil, 2011)
This study deals with fin bamboo plywood panel as an alternative replacement for steel reinforcingwhich is often used in some buildings nowadays by seeing the difference of flexural strengthoccurred in each variation of reinforcement. The experimental procedures are specimens in form offin bamboo plywood panel with length 80 cm, width 45 cm, and height ± 3 cm. Bamboo dimension(1) 1 cm x 1 cm and 0.8 cm x 0.8 cm are 45 cm and 80 cm in length respectively; (2) 0.8 cm x 0.8cm and 0.6 cm x 0.6 cm are 45 cm and 80 cm in length respectively; while (3) 0.6 cm x 0.6 cm and0.5 cm x 0.5 cm are 45 cm and 80 cm in length respectively. Testing is conducted by usinghorizontal panel supported in its four sides by gradually giving concentrated loads in the middle ofthe span in which pedestal spacings are 70 cm and 30 cm respectively and, of course, by using threevariations of reinforcement: 1 cm x 1 cm and 0.8 cm x 0.8 cm; 0.8 cm x 0.8 cm and 0.6 cm x 0.6cm; and the other one is 0.6 cm x 0.6 cm and 0.5 cm x 0.5 cm with 5 specimens in each variations.From statistical analysis, the results of study show that there is no strong influence in flexuralstrength of fin bamboo plywood panel with variation of the bamboo reinforcement. Beside that,there is no significant difference between ultimate load and variation in size of the bambooreinforcement because the reinforcement holds different tension depending on its size due to thecompressive strength of mortal is less than the yield strength of bamboo.